Reduction in Plant Downtime by Applying Lean Manufacturing Methodology’s Value Stream Mapping (VSM) and Single-Minute Exchange of Die (SMED) - Fajardo Cueva, Omar Luis (2025)
This research was conducted in a farinaceous products company that was facing a problem of low productivity due to frequent downtime, leading to underutilization of their capacity. The lean manufacturing methodology was used to address this issue, specifically value stream mapping (VSM) and single-minute exchange of die (SMED) tools. These tools were applied in stages, including a diagnostic pretest (current map), followed by design, implementation, and a posttest (final map). The results were evaluated after the completion of the process, and it was found that the application of SMED led to a significant reduction in downtime. The product changeover time was decreased from 82 minutes to 42 minutes, reducing plant downtime or waste by 40 minutes and improving lean manufacturing indicators.